An Introduction to the Standard Model of Particle Physics - Cottingham, W.N.; Greenwood, D.A. (Cambridge University Press, 2023)
The second edition of this introductory graduate textbook provides a concise yet accessible introduction to the Standard Model. It has been updated to account for the successes of the theory of strong interactions and the observations on matter–antimatter asymmetry. It gives a coherent presentation of the phenomena and theory that describe neutrino mass as well as an account of progress in the theory of strong interactions. The book develops clearly the theoretical concepts from the electromagnetic and weak interactions of leptons and quarks to the strong interactions of quarks. Each chapter ends with problems, with hints to selected problems provided at the end of the book. The mathematical treatments are suitable for graduates in physics, while more sophisticated mathematical ideas are developed in the text and appendices.